Complications of X-ray Endovascular Interventions in Patients with Coronary Heart Disease with Reduced Left Ventricular Systolic Function - Yevhenii V. Aksenov; Ruslan B. Demchenko (Ukrainian Journal of Cardiovascular Surgery, 2021)
The work is dedicated to the research of direct results and immediate possible complications of interventions in X-ray surgery with coronary stent implantation. Our patients with chronic coronary syndrome and reduced left ventricular ejection fraction (LVEF) of less than 40% were studied. The study included 112 patients who were divided into two groups. The first group included 51 patients with LVEF <40% (mean value 32.8 ± 1.14%), the second group involved 61 patients with LVEF >40% (mean value 59.4 ± 1.02%). The mean age of the subjects ranged from 59 to 74 years (mean value 63.85 ± 1.73 years).There were no gender-related differences among the selected patients. There was no statistical difference in comorbidities in both groups. Both groups of patients were examined and managed according to the protocol of diagnosis and treatment adopted at the National Amosov Institute of Cardiovascular Surgery for patients suffering from chronic coronary syndrome.The study results show that patients with coronary artery disease and reduced LVEF 2 times more often developed complications in early postoperative period after PCI with revascularization through stent placement than in group of patients with preserved contractile myocardial function. Duration of PCI procedure and contrast agent use was 26.3±1.4% and 29.8±4.2% higher, respectively; the frequency of life-threatening arrhythmias was 54% higher. Intraoperational signs of acute heart failure developed 4.8 times less often in the control group than in the experimental group. In general, all the patients after stenting achieved good anti-ischemic effect.